The Role of Guidance and Counseling Assessment in Supporting Students' Educational Success - Rustianti, Nora; Putra, Yendri; Hidayat, Rahmat (The Future of Education Journal, 2025)
Assessment in guidance and counseling is a crucial component that serves as the foundation for designing, implementing, and evaluating guidance and counseling services. By conducting a comprehensive assessment, counselors or school guidance teachers can gain a deep understanding of students' characteristics, including academic, social, emotional, and personal aspects. The research method used in this article employs a descriptive qualitative approach in the form of a literature review. This study is based on theories, research, and practices that demonstrate how effective assessment directly contributes to the optimal development of students in the school environment.